2020
DOI: 10.1371/journal.pone.0241340
|View full text |Cite
|
Sign up to set email alerts
|

PrEP discontinuation among Latino/a and Black MSM and transgender women: A need for PrEP support services

Abstract: Purpose Disparities persist in HIV infection among Black and Latino men who have sex with men (BLMSM) and Black and Latina transgender women (BLTW). Increasing uptake and subsequent consistent use of pre-exposure prophylaxis (PrEP), an effective biomedical strategy for preventing HIV acquisition, can dramatically reduce HIV incidence in these populations. The purpose of this study was to explore reasons for PrEP discontinuation among BLMSM and BLTW living in Los Angeles County to inform the development of supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
17

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 41 publications
1
46
0
17
Order By: Relevance
“…Previous research has found that significant racial/ethnic disparities exist in PrEP knowledge and use [26][27][28] particularly among Black/African Americans and the Latinx community and that these disparities are pronounced among trans women [20]. Black trans women made up 15% of the STAY study population, and, in this study, 11% of the participants who reported they were also a STAY study participant were Black (data not shown).…”
Section: Discussionmentioning
confidence: 46%
“…Previous research has found that significant racial/ethnic disparities exist in PrEP knowledge and use [26][27][28] particularly among Black/African Americans and the Latinx community and that these disparities are pronounced among trans women [20]. Black trans women made up 15% of the STAY study population, and, in this study, 11% of the participants who reported they were also a STAY study participant were Black (data not shown).…”
Section: Discussionmentioning
confidence: 46%
“…Furthermore, this was a significant driver of current PrEP use for participants of color, but not for White participants, suggesting that PrEP education from healthcare providers may be particularly important to facilitating PrEP uptake for SMM and trans women of color, who face disproportionate burdens of HIV incidence and prevalence [5]. For providers treating trans women specifically, it is also important to be aware of the unique concerns this population may have, such as concerns related to hormone medications [63,73]. In this sense, providers must broadly be competent in many facets of LGBTQ health, and not only around SMM's needs.…”
Section: Discussion and Implications For Clinical Practicementioning
confidence: 99%
“…Although pre-exposure prophylaxis (PrEP) proves efficacious in reducing HIV transmission, not all populations benefit from the advancement equally [1,2]. Black and Latino men who have sex with men (BLMSM) have lower rates of access and uptake of PrEP compared with their white counterparts [3][4][5][6]. Among MSM qualifying for a PrEP prescription in 2019, Black and Latino men showed 8% and 14% prescription rates, respectively, compared with white men at 63% [7].…”
Section: Introductionmentioning
confidence: 99%
“…These factors are structural health care barriers, such as lack of access, insurance status, and discrimination/racism. Social factors emanating from homophobia, HIV stigma, and additional personal elements within the cultural/community context have also contributed to low PrEP use [5,6,[9][10][11]. Stigma continues to create challenges to PrEP uptake.…”
Section: Introductionmentioning
confidence: 99%